Opinions of Football Referees on the VAR System and VAR Training - Ozer Yıldız; Muhammet Munir Dadı (Türk Spor ve Egzersiz Dergisi)
The purpose of this research is to examine the opinions of football referees who are actively working under the Turkish Football Federation about the video assistant referee (VAR) system and its education. Interview method, one of the qualitative research designs, was used in the research. Research data were collected through a semi-structured interview form developed by the researcher.The research group consists of 20 football referees who are actively working in different classifications determined by maximum diversity sampling, one of the purposive sampling methods, which is one of the non-probability sampling strategies. In the research, the data were evaluated by content analysis method. According to the results of the research, the positive and negative categories of the referees’ thoughts on how the VAR System applied in the world’s major leagues and in our country affect the spirit of the football game and the pleasure of watching; fair decision, the formation of trust, the decrease in the pace of the game and the decrease in the pleasure of watching, they express their opinions against the spirit of football and the adaptation problem and under the name of negative impact categories, respectively; VAR application with a general philosophy of “minimum interference, maximum benefit”, which provides a more systematic and open to advice environment, where the referees express their opinions of self-confident decision, mental comfort, excessive stress and conflict in decision making. In their thoughts that more definite decisions were taken together with the decision diversity and the contribution of the decisions to the game categories; final and clear decisions, variability in interpretations and decisions, decrease in the number of errors, increase in the rate of finding the truth, correction of the decisions affecting the result, objectivity and maximum benefit, the referees expressed their opinions on how the newly implemented VAR System in the world and in our country will contribute to the development of the game in the future. Under the categories of positive contribution and fair play; In their thoughts on the VAR System, which has been in practice in various leagues of the world and in our country for a short time, and the opinions of the referees on the training given to the referees; under the categories of gradual education, being advantageous, being useful and not being sufficient, respectively; increase in the levels of success and education of referees, expert educators and high level opportunity recognition, critical position analysis, upbringing equipped referees, gaining a different perspective and position uncertainty to be examined.